1999
DOI: 10.1088/0953-4075/32/11/310
|View full text |Cite
|
Sign up to set email alerts
|

The fragmentation of core ionized CF4probed by threshold-photoelectron-photoion-photoion coincidence (TPEPIPICO) spectroscopy

Abstract: The ionization and fragmentation of carbon tetrafluoride excited at the C and F 1s thresholds are studied using soft x-ray excitation, threshold electron spectroscopy and state-selective coincidence techniques. The threshold electron spectra reveal indirect low-energy production from pre-edge resonances, and the structure at the thresholds is attributable to post-collision interaction effects, with some evidence of underlying vibrational structure. The coincidence data allow determination of ion and ion pair y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
8
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 23 publications
6
8
0
Order By: Relevance
“…Studies of photon induced reactions include fluorescence measurements [6], photoabsorption [7], photoelectron spectrometry a e-mail: alexander.dorn@mpi-hd.mpg.de [8][9][10][11][12][13][14], threshold photoelectron spectroscopy (TPES) [15][16][17][18], photoion detection [19,20] and various coincidence methods like photoelectron-photoion coincidences (PEPICO) [21][22][23][24], threshold photoelectron-photoion coincidences (TPEPICO) [4,25,26] and threshold photoelectron-fluorescence coincidences (TPEFCO) [5]. Photo double ionization was studied using photoion-photoion coincidences (PIPICO) [27][28][29], photoelectron-photoelectron coincidences (PEPECO) [30] and threshold photoelectron-photoion-photoion coincidences after core ionization (TPEPIPICO) [31]. There are also studies reported on negative ion fragment formation by photons [32].…”
Section: Introductionmentioning
confidence: 99%
“…Studies of photon induced reactions include fluorescence measurements [6], photoabsorption [7], photoelectron spectrometry a e-mail: alexander.dorn@mpi-hd.mpg.de [8][9][10][11][12][13][14], threshold photoelectron spectroscopy (TPES) [15][16][17][18], photoion detection [19,20] and various coincidence methods like photoelectron-photoion coincidences (PEPICO) [21][22][23][24], threshold photoelectron-photoion coincidences (TPEPICO) [4,25,26] and threshold photoelectron-fluorescence coincidences (TPEFCO) [5]. Photo double ionization was studied using photoion-photoion coincidences (PIPICO) [27][28][29], photoelectron-photoelectron coincidences (PEPECO) [30] and threshold photoelectron-photoion-photoion coincidences after core ionization (TPEPIPICO) [31]. There are also studies reported on negative ion fragment formation by photons [32].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, topics such as the relative intensities of transitions from core levels to antibonding molecular orbitals or Rydberg states, Jahn-Teller and quasi-Jahn-Teller coupling, and the dissociative nature of core-excited intermediate states and valence-ionized final states have been discussed in several papers (see, e.g., [1][2][3][4][5][6][7][8] for CH 4 , [9][10][11][12][13][14][15][16][17][18][19] for CF 4 , and [4,15] for CCl 4 ). A summary of the electronic properties of all three molecules is given in [20] together with high-resolution photoabsorption data.…”
Section: Introductionmentioning
confidence: 99%
“…However, the threshold for double ionization is 38 eV [25], which is somewhat lower than the lowest state populated by the Auger decay of CF 4 + (1s −1 ) which occurs at 44 eV [14]. The higher KER peak at 7.5 eV [26] is probably coming from a higher lying state which is directly dissociating, e.g., a dication state with an electron removed from one of the bonding C-F σ orbitals, for which earlier calculations indicate there are many candidates in this energy range [27].…”
mentioning
confidence: 88%